EU Citizenship and EU Entities: New Perspectives for Citizens and Companies - Guzewicz, Agnieszka (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
This paper describes the relationship that might be established between the statuses of EU citizenship (natural persons) and “EU entities” (companies) in the context of exercising the freedom of establishment. Just as natural persons may invoke EU citizenship (that is to say an identity resulting from European Union membership), companies too should have the right to claim supranational identity resulting from their relationship with the EU legal order. Recent changes in the approach to the notion of EU citizenship could also influence the development of European company law.
Keywords: obywatelstwo UE; podmioty UE; spółki; osoby fizyczne; swoboda przedsiębiorczości